Original paperDevelopment of Parents’ of Children with Hymenoptera Venom Allergy Quality of Life Scale (PoCHVAQoLS) - Brzyski, Piotr; Cichocka-Jarosz, Ewa; Lis, Grzegorz; Tobiasz-Adamczyk, Beata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: Venom allergy in children, as a potentially life-threatening disease, may have a considerable impact on the quality of life of the parents of the affected patients. Aim : To present development of the quality of life scale for such parents. Material and methods: The study sample included 70 parents of children with a history of insect sting reaction, referred for consultations to the allergy centre of the University Children’s Hospital of Krakow, Krakow, Poland, in 2000–2010. An initial pool of 56 items divided into 6 domains was prepared. The items with intercorrelations higher than 0.7 were removed from each domain and principal component analysis was conducted for each domain separately to provide a one-dimensional subscale for each domain. Reliability of the subscales was assessed using the Cronbach  coefficient in terms of the Classical Test Theory and with the rho coefficient in terms of the Item Response Theory. The multidimensionality of the scale was tested using multitrait scaling. Results : Two to four items from each domain were selected to constitute five subscales. Both the rho and  coefficients for all the subscales were 0.75 or higher. The multitrait method showed that almost all the items indicated stronger correlations with their own subscale than with other subscales. Correlations between subscales were lower than 0.5. Conclusions : The presented scale consists of high validity and reliability subscales measuring the quality of life of parents of Hymenoptera venom allergic children. As their quality of life is strongly related to the health of their children, such information may be helpful in everyday clinical practice.